Analisis Dampak Revitalisasi Penggilingan Padi Skala Kecil Terhadap Pendapatan dan Kelembagaan Petani Sumatera Barat - Donna Gracia Jorie; Widya Fitriana; Endry Martius (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2026)
Small Rice Mills (PPK) are an important link in the national rice supply chain, but most PPKs in West Sumatra province have technological limitations with an average yield of only 40% - 45%, far below the SNI yield. This study aims to analyze the impact of PPK revitalization on farmers' income and farmer institutions in West Sumatra. The research method used a survey within a case study with a qualitative and quantitative (before-after) approach on the Tanjung Mutiara Farmer Group in Tanah Datar Regency and the Karakek Indah Farmer Group in Pesisir Selatan Regency with a total of 69 respondents. The results show that PPK revitalization significantly increased rice yields from 40%–45% to 61%–70%, reduced losses by 20%–25%, and improved rice quality from grade 2–3 to grade 1 (Premium). Farmers' income increased by 65% to 69.5% with a significant t-test result (p-value = 0.000). In addition, the participation of farmer group members increased from 24% to 50% to 80% to 100%, and business integration was formed within farmer institutions. It was concluded that the revitalization of PPK had a significant impact on increasing farmer income and farmer institutions.